Short-term evaluation of an intra-articular technique for cranial cruciate ligament rupture in dogs using nylon or polyester - Prada, Tiago Carmagnani [UNESP]; Da Silva, Anderson Coutinho; Minto, Bruno Watanabe [UNESP] (Universidade Estadual de Londrina, 2018)
Cranial cruciate ligament rupture (CCrLR) is a common condition found in the small animal routine, being correlated to traumas, obesity, genetic factors, and primary osteoarthritis (OA) in dogs. Affected animals show articular instability that, if not corrected surgically, may cause secondary OA and loss of limb function. The aim of this study was to compare short-term results of the intra-articular technique for knee stabilization after CCrLR using a surgical button associated with polyester yarn (Group A), the surgical button associated with nylon yarn (Group B), and surgical toggle associated with polyester yarn (Group C). Eighteen dogs presenting CCrLR, weight varying from 5 to 35 kg, and different sex and breed were divided into three groups of six individuals. OA radiographic grade, pre- and post-operative lameness, surgical time, and the macroscopic aspect of cartilage were assessed. The intra-articular technique was performed by passing a suture through two tunnels, drilled in the femoral condyle and tibial crest to stabilize the knee joint. Twelve animals presented a decreased lameness and normal limb function after 15 days. On the other hand, four dogs from Group B presented complications: two dogs had suture rupture after 30 days and other two showed muscular contracture with decreased range of motion, followed by loss of limb function. In Group A, one dog showed suture rupture after 15 days and other had suture infection after 30 days. In Group C, dogs recovered normal limb function without complications. Therefore, surgical toggle associated with polyester yarn was better than the other studied materials.
Keywords: CCLR; Knee joint; Orthopedic; Osteoarthritis